Shirk in the era of Gen Z: Challenges and strategies for Muslim ( Qs. An- Nisa : 48 ) - Ilham Abiyusuf; Fadhli Maulana Ihsan; Wahyu Saputra; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
Background. Shirk, or associating partners with Allah, is a major challenge for Gen Z Muslim youth who are influenced by social media, consumerist culture and secular ideologies. These influences can trigger behaviors that go against tawhid, such as celebrity idolization and materialism. Therefore, effective strategies are needed to strengthen religious understanding and maintain commitment to tawhid amidst the challenges of the modern era. Purpose. This research aims to identify the challenges and strategies faced by the Gen Z Muslim youth in avoiding shirk in the present era. Specifically, this research analyzes the factors influencing the tendency towards contemporary forms of shirk, and seeks effective solutions to strengthen the understanding of the principle of tawhid, using a case study based on Qs An – Nisa verse 48. Method. The research method used is a qualitative method, by analyzing documents. Data was obtained from various literatures discussing shirk, as well as the shirk occurring in the Gen Z era. It also connects this with the Quranic text Qs An - Nisa verse 178. Analysis was conducted to identify new forms of polytheism, as well as the challenges and strategies to avoid it.. Results. Shirk, associating partners with Allah, is Islam's gravest sin, unforgivable without repentance. It includes major shirk (idol worship) and minor shirk (showing off in worship). Modern forms arise from technology and self-worship. The Qur'an (An-Nisa [4]: 48) stresses its contradiction to monotheism. Conclusion. Shirk challenges Gen Z faith amid technological advances, social media, and identity crises, risking subtle polytheism. This study emphasizes understanding shirk to preserve monotheism and strengthen faith. Creative, relevant religious education is vital to help youth navigate spiritual challenges in the modern era.